Kemampuan Mengidentifikasi Unsur-Unsur Surat Dinas Siswa Kelas VII SMP YLPI Marpoyan Kota Pekanbaru - Christiana Ratna; Desi Sukenti (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The research title is “Ability to Identify Elements of a Class VII Student Service Lettar at YLPI Marpoyan Middle School”. Pekanbaru City”.Formulation of the problem: How is the student’s ability to identify theelements of an official letter for class VII students of SMP YLPI Marpoyan Pekanbaru City. Stra the objective is to collect data and informan about students’ ability to identify the elements of official letters for classVII students of SMP YLPI Marpoyan Pekanbaru City. Descriptive method with a quantitative approach is classified into the type of field research. The theory used is the definition of identifying, understanding letters, understanding official letters, elements of official letters, letter functions, correct and good letter requirements, letter language, characteristics of official letters, froms of official letters and parts of official letters. Sources YLPI Marpoyan Middle S chool Students, Pekanbaru City. Data collection techniques are observation techniques, test techniques and documentation. The data analysis technique is about the students’ability to identify the elements of the seventh grade official letter at SMP YLPI Marpoyan Pekanbaru City. The elements of an official letter are: letter head, letter number, letter date, letter attachment, letter subject, letter address, letter opening greeting, letter connntent, letter closing greeting, letter ransom. Class VII-1 students are categorized as getting very good grades seen from the classsification of student assessments getting 85-100.